2000
DOI: 10.1046/j.1365-2672.2000.00969.x
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial agents from plants: antibacterial activity of plant volatile oils

Abstract: The volatile oils of black pepper [Piper nigrum L. (Piperaceae)], clove [Syzygium aromaticum (L.) Merr. & Perry (Myrtaceae)], geranium [Pelargonium graveolens L'Herit (Geraniaceae)], nutmeg [Myristica fragrans Houtt. (Myristicaceae), oregano [Origanum vulgare ssp. hirtum (Link) Letsw. (Lamiaceae)] and thyme [Thymus vulgaris L. (Lamiaceae)] were assessed for antibacterial activity against 25 different genera of bacteria. These included animal and plant pathogens, food poisoning and spoilage bacteria. The volati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

111
1,979
9
134

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 3,388 publications
(2,350 citation statements)
references
References 57 publications
111
1,979
9
134
Order By: Relevance
“…Other minority compounds also possess antimicrobial properties, such as cariophyllene (Ayoola et al 2008). Thus, Dorman and Deans (2000) state that the oils' antimicrobial activity is related to the composition of the plant's volatile oils, the structural configuration of the oils' constituent compounds and their functional groups and potencial synergistic interactions among the compounds. In the case of cumin EO it was observed that E. coli and S. enteritidis Typhimurium had high MIC levels (750 mg/L).…”
Section: Antimicrobial Activity Of Essential Oils and Functional Extrmentioning
confidence: 99%
“…Other minority compounds also possess antimicrobial properties, such as cariophyllene (Ayoola et al 2008). Thus, Dorman and Deans (2000) state that the oils' antimicrobial activity is related to the composition of the plant's volatile oils, the structural configuration of the oils' constituent compounds and their functional groups and potencial synergistic interactions among the compounds. In the case of cumin EO it was observed that E. coli and S. enteritidis Typhimurium had high MIC levels (750 mg/L).…”
Section: Antimicrobial Activity Of Essential Oils and Functional Extrmentioning
confidence: 99%
“…Exceptional ways to available antibiotics for disease management have been increasingly felt due to the increase in the resistance of bacterial isolates. This has urgently demanded the requirement of second and third line drug and plants are considered potent candidates to overcome such inevitable problems associated with the complications of antimicrobial resistant bacteria [3][4][5][6][7][8][9][10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
“…The activity of essential oils is related to the respective composition, the structural configuration of the constituent components of the volatile oils and their functional groups, and the possible synergistic interactions between components [17]. In the literature, some studies reported that components with phenolic structures, such as eugenol and thymol are known to possess some antimicrobial activities as bactericidal or bacteriostatic agents against gram-positive and gramnegative bacteria, and also against yeasts [13,14,[17][18][19]. In this job, the analysis of the antimicrobial activity on the microorganisms of the unlighted agents confirmed that phenols (eugenol and thymol) were the most potent antimicrobial agents.…”
Section: Discussionmentioning
confidence: 99%
“…biological activities, among others, are basic questions to learn the antimicrobial action and compare results [16,17]. The properties of the essential oils are determined by the basic structure of the main component and its functional groups.…”
mentioning
confidence: 99%
See 1 more Smart Citation